2017
DOI: 10.1038/s41598-017-13080-1
|View full text |Cite
|
Sign up to set email alerts
|

Collision with duplex DNA renders Escherichia coli DNA polymerase III holoenzyme susceptible to DNA polymerase IV-mediated polymerase switching on the sliding clamp

Abstract: Organisms possess multiple DNA polymerases (Pols) and use each for a different purpose. One of the five Pols in Escherichia coli, DNA polymerase IV (Pol IV), encoded by the dinB gene, is known to participate in lesion bypass at certain DNA adducts. To understand how cells choose Pols when the replication fork encounters an obstacle on template DNA, the process of polymerase exchange from the primary replicative enzyme DNA polymerase III (Pol III) to Pol IV was studied in vitro. Replicating Pol III forming a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Scotland et al () showed that the switch requires that Pol IV contact not only two discrete sites on the β clamp protein, but Pol III as well. Impaired Pol III–ssDNA interactions (e.g., when polymerase encounters a hairpin‐stem duplex) influence the susceptibility of Pol III HE to Pol IV‐mediated polymerase exchange (Le et al, ). Using single‐molecule time‐lapse microscopy to directly visualize fluorescently labeled pol IV in live cells, Henrikus et al () recently demonstrated that over 90% of foci induced by DNA damage form outside of replisome regions, suggesting that pol IV predominantly carries out non‐replisomal functions, consistent with the postreplicative TLS in gaps behind the replisome model.…”
Section: Tls Polymerasesmentioning
confidence: 99%
“…Scotland et al () showed that the switch requires that Pol IV contact not only two discrete sites on the β clamp protein, but Pol III as well. Impaired Pol III–ssDNA interactions (e.g., when polymerase encounters a hairpin‐stem duplex) influence the susceptibility of Pol III HE to Pol IV‐mediated polymerase exchange (Le et al, ). Using single‐molecule time‐lapse microscopy to directly visualize fluorescently labeled pol IV in live cells, Henrikus et al () recently demonstrated that over 90% of foci induced by DNA damage form outside of replisome regions, suggesting that pol IV predominantly carries out non‐replisomal functions, consistent with the postreplicative TLS in gaps behind the replisome model.…”
Section: Tls Polymerasesmentioning
confidence: 99%